Comparison of Neutralizing Dengue Virus B Cell Epitopes and Protective T Cell Epitopes With Those in Three Main Dengue Virus Vaccines - Pinheiro, Josilene Ramos; Camilo dos Reis, Esther; Souza, Rayane da Silva Oliveira; Rocha, Ana Luíza Silva; Suesdek, Lincoln; Azevedo, Vasco; Tiwari, Sandeep; Rocha, Beatriz Gonçalves Silva; Birbrair, Alexander; Méndez, Erick Carvalho; Luiz, Wilson Barros; Amorim, Jaime Henrique (Frontiers in Immunology, 2021)
The four serotypes of Dengue virus (DENV1-4) are arboviruses (arthropod-borne viruses) that belong to the Flavivirus genus, Flaviviridae family. They are the causative agents of an infectious disease called dengue, an important global public health problem with significant social-economic impact. Thus, the development of safe and effective dengue vaccines is a priority according to the World Health Organization. Only one anti-dengue vaccine has already been licensed in endemic countries and two formulations are under phase III clinical trials. In this study, we aimed to compare the main anti-dengue virus vaccines, DENGVAXIA®, LAV-TDV, and TAK-003, regarding their antigens and potential to protect. We studied the conservation of both, B and T cell epitopes involved in immunological control of DENV infection along with vaccine viruses and viral isolates. In addition, we assessed the population coverage of epitope sets contained in each vaccine formulation with regard to different human populations. As main results, we found that all three vaccines contain the main B cell epitopes involved in viral neutralization. Similarly, LAV-TDV and TAK-003 contain most of T cell epitopes involved in immunological protection, a finding not observed in DENGVAXIA®, which explains main limitations of the only licensed dengue vaccine. In summary, the levels of presence and absence of epitopes that are target for protective immune response in the three main anti-dengue virus vaccines are shown in this study. Our results suggest that investing in vaccines that contain the majority of epitopes involved in protective immunity (cellular and humoral arms) is an important issue to be considered.